Review on volumetric energy density: inluence on morphology and mechanical properties of Ti6Al4V manufactured via laser powder bed fusion - Buhairi, Minhalina Ahmad; Mohd Foudzi, Farhana; Jamhari, Fathin Iliana; Sulong, Abu Bakar; Mohd Radzuan, Nabilah Afiqah; Muhamad, Norhamidi; Mohamed, Intan Fadhlina; Azman, Abdul Hadi; Wan Sharuzi, Wan Harun; M.S.H., Al-Furjan (Springer Science and Business Media Deutschland GmbH, 2023)
Various laser powder bed fusion (LPBF) process parameters must be considered as they can independently affect the properties of end-product. However, many studies simply examine one or two LPBF process parameters. Laser power, scan speed, scan spacing, and layer height are the four primary LPBF process parameters that contribute to volumetric energy density (VED) used in LPBF. VED is often used as an optimization metric for LPBF process parameters, because it takes all four major parameters into consideration. Thus, this paper focuses on the effect of VED on the morphology and properties of part, and also discusses on the interrelationship between all four parameters. Common range used for each parameter is 70–400 W for laser power, 70–1800 mm/s for scan speed, 50–140 µm for scan spacing, and 20–50 µm for layer height. It can be seen as the VED increased, the microstructure of as-built titanium alloy Ti6Al4V components exhibited smaller α’ martensite size and larger columnar β grain. High VED can also reduce porosity and defect formation, which will help in increasing part density. The lowest surface roughness reported for LPBF Ti6Al4V is 4.91 µm. Meanwhile, the maximum microhardness obtained is 443 HV and the highest tensile strength achieved is 1400 MPa. The VED used for studies that obtained these results are in the range of 55–65 J/mm3. Thus, it can be concluded that the most suitable VED for LPBF printing of Ti6Al4V is around 55–65 J/mm3.